Assessment of four organophosphorus pesticides as inhibitors of human acetylcholinesterase and butyrylcholinesterase - Tena Čadež (Nature Portfolio, 2021)
Abstract Toxicity of organophosphorus compounds (OPs) remains a major public health concern due to their widespread use as pesticides and the existence of nerve agents. Their common mechanism of action involves inhibition of enzymes acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) which are crucial for neurotransmission. Both chronic and acute poisoning by OPs can leave long-lasting health effects even when the patients are treated with standard medical therapy. Therefore, an increasing urgency exists to find more effective oxime reactivators for compounds which are resistant to reactivation, especially phosphoramidates. Here, we investigated in silico and in vitro interactions and kinetics of inhibition for human cholinesterases with four organophosphate pesticides—ethoprophos, fenamiphos, methamidophos and phosalone. Overall, ethoprophos and fenamiphos displayed higher potency as inhibitors for tested cholinesterases. Our results show that methamidophos-inhibited hAChE was more susceptible to reactivation than hAChE inhibited by fenamiphos by selected oximes. Molecular modelling enabled an evaluation of interactions important for specificity and selectivity of both inhibition and reactivation of cholinesterases. Two newly developed reactivators—bispyridinium triazole oxime 14A and zwitterionic oxime RS194B possess remarkable potential for further development of antidotes directed against pesticides and related phosphoramidate exposures, such as nerve agents tabun or Novichoks.